RISK FACTORS RELATE OF OVARIAN CANCER IN WOMEN : LITERATURE REVIEW - Agustin Agustin; Yanti Hermayanti; Ida Maryati; Henny Suzanna Mediani (Journal of Maternity Care and Reproductive Health, 2021)
Every woman is at risk for ovarian cancer. Until now, ovarian cancer is the 3rd of the 10 most common cancers in women. If exposed, it can cause complex problems until death occurs. For that every woman needs to be aware of this disease by recognizing the risk factors. The purpose of this study is to explore these various factors through a review of related literature through searches of thedatabases Pubmed, Science Direct, Willey, and Cambrige with a total of 10 analysis articles originating from America, China, Taiwan, Europe, Alaska, England and Finland. By searching for articles according to the inclusion criteria, namely full text, published in 2010 - 2020, articles having DOIs, experimental research designs and case studies, using the keywords risk factor and ovarian cancer. The results obtained 602 articles, and 10 articles describing the incidence of ovarian cancer were proven to be related to an imbalance of FSH, estrogen and progesterone hormones, the use of cosmetic products on the face and genetalia containing asbestos, and a family history of cancer. Based on these results, women should immediately get checked out if there are hormonal disorders such as disrupted menstrual cycles, and not use cosmetic products that contain asbestos, and observe symptoms from an early age if the family has had ovarian cancer or breast cancer. Conclusion: by knowing the risk factors, each woman can assess the risk factors that are present in her, so that she can do early detection of ovarian cancer and immediately get therapy if ovarian cancer is found quickly and precisely This research can be continued by focusing more research on factors of hormonal and non-hormonal contraceptive use.